(untitled) (European Bison Conservation Newsletter, 2015)
European bison increasingly face a number of reproduction disorders. It can result in an increased risk of their extinction. Thus, microbiological analysis of vaginal swabs seems to be an important diagnostic method in monitoring of European bison reproductive tract infections. However, the first research in this area was carried out only by Speck et al. in 2006, but its results are uncompleted. Thus, the aim of this study was the continuation of research on E. bison vaginal cytology extended by microbiological examination and correlation of obtained results. The female E. bison included in our study came from either free ranging herd or enclosures. They were divided into three groups. The first group consisted of animals without any lesions in reproductive tract. Animals from the second group had pathological lesions in genital organs. The third group included pregnant females. Cytological and microbiological samples were collected from vaginal mucosa with a sterile swab from all individuals. Microbiological analysis of vaginal swabs provided less specific test compared to vaginal cytology, as most of isolated bacteria species were found in all examined groups of E. bison females with equal frequency. However, in animals with gross pathological lesions, the characteristic changes in vaginal cytology confirming necropsy, were observed.